2005
DOI: 10.1097/00124645-200505000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Care at the Time of Death

Abstract: Nurses are exposed to death across the lifespan ranging from stillbirths to neonatal deaths to deaths of children, adolescents, or adults from trauma or various acute or chronic illnesses. To provide quality care at the end of life, nurses must not only possess the knowledge and skills to provide effective end-of-life care, but must also develop the attitudes and interpersonal competence to provide compassionate care. The purpose of this article is to present the key content and teaching strategies related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(4 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…women scored higher, which was different from previous studies [35]. As we all know, hospice care services require healthcare providers not only to master professional knowledge and skill but also to have the ability to empathize with dying patients and their families [29,30,36]. From the perspective of caring ethics, men prefer to look for answers logically.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…women scored higher, which was different from previous studies [35]. As we all know, hospice care services require healthcare providers not only to master professional knowledge and skill but also to have the ability to empathize with dying patients and their families [29,30,36]. From the perspective of caring ethics, men prefer to look for answers logically.…”
Section: Discussioncontrasting
confidence: 61%
“…Therefore, it's suggested that hospitals should carry out hospice care training to make up for the lack of hospice care in school education. In consideration of there is less professional training on hospice care in China at present, it's recommended hospitals refer to successful experiences in other cou ntries, such as the "Quality End of Life Care for All (QELCA)" training launc hed by St Christopher's Hospice in the UK [29], and the "End-of-life Nursing Education Consortium (ELNEC)" course from the USA [30]. Reframing hospice as a choice to focus on how to live rather than how long to live may help d evelop hospice care.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it's suggested that hospitals should carry out hospice care training to make up for the lack of hospice care in school education. In consideration of there is less professional training on hospice care in China at present, it's recommended hospitals refer to successful experiences in other countries, such as the "Quality End of Life Care for All (QELCA)" training launched by St Christopher's Hospice in the UK [ 33 ], and the "End-of-life Nursing Education Consortium (ELNEC)" course from the USA [ 34 ]. As early as 2016, the Beijing Living Will Promotion Association (LWPA) began collaborating with St. Christopher's Hospice to promote the QELCA training in China [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ecco che, alle specifiche e avanzate conoscenze e abilità tecniche proprie dell'assistenza di emergenza, l'infermiere di Pronto Soccorso deve affiancare qualità e competenze interpersonali per poter fornire la migliore assistenza di fine vita, per poter supportare i familiari nelle pri-missime fasi iniziali di elaborazione del lutto e, non ultimo, per sviluppare modalità positive di controllo dello stress emozionale correlato alle esperienze vissute. 11,12 Attraverso l'analisi della letteratura internazionale si è voluto centrare l'attenzione sui diversi fattori che possono entrare in gioco nell'assistenza di fine vita in Pronto Soccorso, ma anche sulle emozioni e i vissuti sperimentati dagli infermieri di emergenza di fronte all'evento morte.…”
Section: Introduzioneunclassified